Educational Homogamy and Assortative Mating Have Not Increased - Rania Gihleb; Kevin Lang (Institute of Labor Economics (IZA), 2016)
Some economists have argued that assortative mating between men and women has increased over the last several decades, thereby contributing to increased family income inequality. Sociologists have argued that educational homogamy has increased. We clarify the relation between the two and, using both the Current Population Surveys and the decennial Censuses/American Community Survey, show that neither is correct. The former is based on the use of inappropriate statistical techniques. Both are sensitive to how educational categories are chosen. We also find no evidence that the correlation between spouses' potential earnings has changed dramatically.
Keywords: J12; 330; assortative mating